Greece: the Crisis goes to the Theatre (Itinera, 2019)
How has the economic crisis affected the theatre in Greece? In the recent years, Athens and Thessaloniki have experienced a boom in culture and theatre. Despite low budgets (young actors are often unpaid), the number of plays performed is set to increase and the new production strategies are attracting more audience. The polis itself has become the stage: performances are taken out of the theatres and moved to public squares, streets, old factories and rundown neighbourhoods. Meanwhile, the citizens-spectators have rediscovered the urban topography and the renewed sense of community. It seems that bearing together the brunt of the crisis is possible.